2008
DOI: 10.1002/zamm.200700149
|View full text |Cite
|
Sign up to set email alerts
|

Antiplane shear deformations of an anisotropic elliptical inhomogeneity with imperfect or viscous interface

Abstract: Based on the Lekhnitskii-Eshelby approach of two-dimensional anisotropic elasticity, a semi-analytical solution is derived for the problem associated with an anisotropic elliptical inhomogeneity embedded in an infinite anisotropic matrix subjected to remote uniform antiplane shear stresses. In this research, the linear spring type imperfect bonding conditions are imposed on the inhomogeneity-matrix interface. We use a different approach than that developed by Shen et al. (2000) to expand the function encounter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Ting [10] concluded that displacement oscillation is independent of the individual orientation of the two materials and is dependent on the material properties only. Anti-plane loading problem with a crack at the interface of the orthotropic strips was tackled in [14,15]. The analysis of the co-existence of multiple cracks in anisotropic materials is a complex phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Ting [10] concluded that displacement oscillation is independent of the individual orientation of the two materials and is dependent on the material properties only. Anti-plane loading problem with a crack at the interface of the orthotropic strips was tackled in [14,15]. The analysis of the co-existence of multiple cracks in anisotropic materials is a complex phenomenon.…”
Section: Introductionmentioning
confidence: 99%